Students with learning disabilities/attention-deficit/hyperactivity disorder in higher education dealing with remote learning: lessons learned from COVID-19 era - Sarid, Miriam; Lipka, Orly (Frontiers in Psychology, 2023)
Introduction The current study aimed to examine how students with learning disabilities (LD) and/or attention-deficit/hyperactivity disorder (ADHD) adjusted to higher education during the transition to remote learning (RL) in Israel during the COVID-19 pandemic. Methods The study involved 621 undergraduate students, 330 of whom participated during the COVID-19 pandemic and 291 before the pandemic. Among these students, 198 had been diagnosed with LD and/or ADHD, while 423 had no reported disabilities (control group). Results Students with LD/ADHD generally had lower adjustment scores during face-to-face learning and RL than the control group. In-depth analyses of four subgroups revealed that students with LD + ADHD reported lower academic, emotional, and institutional adjustments as well as reported lower satisfaction with life during RL than the control group members. ADHD was found to directly predict low satisfaction with life through the mediation of adjustment scores. Discussion In conclusion, it is recommended that support be provided to high-risk LD/ADHD populations during a crisis. Furthermore, the implication of this study can inform intervention during emergency times.